Proactive dynamic virtual-machine consolidation for energy conservation in cloud data centres - Ismaeel, Salam; Karim, Raed; Miri, Ali (Journal of cloud computing : advances, systems and applications, 2018)
Data center power consumption is among the largest commodity expenditures for many organizations. Reduction of power used in cloud data centres with heterogeneous physical resources can be achieved through Virtual-Machine (VM) consolidation which reduces the number of Physical Machines (PMs) used, subject to Quality of Service (QoS) constraints. This paper provides an in-depth survey of the most recent techniques and algorithms used in proactive dynamic VM consolidation focused on energy consumption. We present a general framework that can be used on multiple phases of a complete consolidation process.